The effectiveness of the nominating ideas strategy in the collection of history for fourth-grade literary students - Alhasan, Muntaha Abdulkareem Mohammed; Shoukry, Parwin Mahmoud (Al-Adab Journal, 2021)
The aim of the research is to identify the effectiveness of the idea-nomination strategy in the achievement of history by second-grade intermediate students. To achieve the goal of the research, the researcher used the experimental design of the two equivalent groups (experimental and control), as the two divisions (A and B) were randomly selected as a sample for the research of second-grade students The average in the mean of the meanings for the girls that were randomly selected, was done The two groups are equivalent in variables (age in months, intelligence, scores for the first course) and the t-test was calculated and the results were not statistically significant. The research sample consisted of (60) students, (30) students in the experimental group and (30) in the control group. The students of the two groups studied the history book for the second intermediate grade for a period of twelve weeks, at two lessons per week The students of the experimental group using the strategy of nominating ideas and the students of the control group studied in the usual way, the researcher prepared an achievement test, and their validity and stability were verified and applied after the end of the experiment. Results: There were statistically significant differences between the mean test scores in the history subject between the female students of the experimental and control groups and for the benefit of the experimental group students. In light of the results, the researcher concluded the effect of the strategy of nominating ideas on the collection of history for second-grade students, mediation, and recommended several recommendations, including the use of the strategy of nominating ideas in teaching and training teachers to use it.